Studi Kritis Konsep dan Aplikasi Pembinaan Mental Tentara Nasional Indonesia Angkatan Darat (TNI AD) - Ilyas, Asmil; Saepudin, Didin; Ibdalsyah, Ibdalsyah (Ta'dibuna: Jurnal Pendidikan Islam, 2013)
The Army Mental Building is an institution within the Army that has duties and obligations to build mental Soldiers, civil servants and their family to realize moral superiority, solidity and professionalism of the soldiers. In developing mental coaching, Indonesian army has been to try and make the various models in order to develop a better system. However, in reality, there are many elements of the army (especially in the Military District that be focus of research) that perform actions incompatible with the moral religion and the state. The main cause is less appropriate to the circumstances and the root of the problem in education and Islamic mental spiritual building. Therefore, if someone understands well about Islam, so he will be able to behave more polite, away from bad practice (munkar) and avoid violence to not abuse all the mandate to be implemented. Islamic Mental Spiritual building is only done as contained in the document published by the Army Mental Development Department, which contains the teachings of Islam. Nearly 80% of it is the procedure of worship. The remaining are monotheistic doctrine. In addition, the system uses only speech teaching and not use any other study. Educational media are still using conventional systems. Therefore, there is need for improvement in the Islamic mental spiritual building, especially in the field of matter, teachers, systems and tools used. The materials presented on theology and morals should be taught critically by showing some indications, not used as a doctrine to be followed. This is related to the maturity level of the members of the Indonesian Army. The teachers have to follow a specified curriculum and researched as needed. On the other hand, teachers should be using some interesting methods. System lesson that had only the general should be converted into structured in terms of time, place and participants. It can enhance the understanding of the army. In addition, all members must follow it continuously without having to be disturbed by other activities that are not urgent. On the other hand is Duty of Devision Head of Islamic mental building (Kasibinrohis) to improve the competence of educators who owned so the more creative and innovative. Kasibinrohis should also always carry good coordination by the Command and other units, so that all programs can be realized by well-planned. Kasibinrohis also need to enhance cooperation with the surrounding community. This is necessary because the public also has an influence on the religious attitude of the army and the civil servants especially in the Army Military District. Kasibinrohis should also pay attention critics, suggestions and feedback from the soldiers, all of which can be used as a improvement of the system for the evaluation of mental Building, especially in the Army Military District.